'Green' on the ground but not in the air: Pro-environmental attitudes are related to household behaviours but not discretionary air travel. (January 2017) - Alcock, Ian; White, Mathew P.; Taylor, Tim; Coldwell, Deborah F.; Gribble, Matthew O.; Evans, Karl L.; Corner, Adam; Vardoulakis, Sotiris; Fleming, Lora E.
Highlights: Relationships between pro-environmentalism and air travel were explored using two UK surveys. Climate concern and environmental attitude were not related to propensity to fly. The propensity to fly was not related to pro-environmental household behaviours. Pro-environmentalism among air travellers was not related to distances flown. Pro-environmental attitudes were related to pro-environmental household behaviours. Abstract: The rise in greenhouse gas emissions from air travel could be reduced by individuals voluntarily abstaining from, or reducing, flights for leisure and recreational purposes. In theory, we might expect that people with pro-environmental value orientations and concerns about the risks of climate change, and those who engage in more pro-environmental household behaviours, would also be more likely to abstain from such voluntary air travel, or at least to fly less far. Analysis of two large datasets from the United Kingdom, weighted to be representative of the whole population, tested these associations. Using zero-inflated Poisson regression models, we found that, after accounting for potential confounders, there was no association between individuals' environmental attitudes, concern over climate change, or their routine pro-environmental household behaviours, and either their propensity to take non-work related flights, or the distances flown by those who do so. These findings contrasted with those for pro-environmental household behaviours, where associations with environmental attitudes and concern were observed. Our results offer little encouragement for policies aiming to reduce discretionary air travel through pro-environmental advocacy, or through 'spill-over' from interventions to improve environmental impacts of household routines.